IMPLEMENTASI ALGORITMA LEVENBERG–MARQUARDT DALAM PREDIKSI DINI PENYAKIT KARDIOVASKULAR - Wijaya, Edi (Universitas Methodist Indonesia, 2023)
Heart disease or also known as cardiovascular disease are all diseases that occur due to impaired heart function. Heart disease is the result of plaque buildup in the coronary arteries, which blocks blood flow to the heart and increases the risk of heart attack and other complications. Cardiovascular disease due to atherosclerosis is a challenge in itself because this type of disease is a progressive disease that can be modified by various actions and only causes few symptoms until the end of the course of this disease but when this disease is clinically proven, there is only a short duration between the time of onset of symptoms and pain, disability, even death. Risk factors for cardiovascular disease begin at a young age, even when a person has no symptoms and is not aware of the consequences of these risk factors. This Early Cardiovascular Disease Prediction application implements the Levenberg Marquardt algorithm in a cardiovascular disease grouping system so that the search process requires a relatively fast time. This Cardiovascular Disease Early Prediction application can be accessed easily using a smartphone so that users can access it quickly and efficiently.